2017
DOI: 10.21202/1993-047x.11.2017.4.146-169
|View full text |Cite
|
Sign up to set email alerts
|

The Failure of Mandated Disclosure, part 4

Abstract: Цель: разработка концептуальных теоретико-правовых положений и научных рекомендаций по обоснованию не-эффективности требования раскрытия информации. Методы: всеобщий диалектический метод познания, а также основанные на нем общенаучные и частноправовые методы исследования. Результаты: в статье рассматриваются достоинства и недостатки самого распространенного в современном обществе метода защиты личной автономии: требования обязательного раскрытия информации. Статья состоит из четырех раз-делов: (1) разносторонн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…Esto unido a la posibilidad de abordar la problemática mediante el uso remedios neutrales con respecto al funcionamiento del mercado 40 explica, en primer lugar, porqué, desde sus orígenes 41 , la normativa de consumo ha consagrado el derecho a la información como un fundamento esencial de la protección contractual del consumidor tanto en su normativa general como sectorial 42 . Y, segundo, porqué las medidas encaminadas a proteger el consumidor vulnerable adoptan una estrategia basada en el recurso a los deberes de información 43 .…”
Section: Consumidores Y Usuarios Frente a Situaciones De Vulnerabilid...unclassified
“…Esto unido a la posibilidad de abordar la problemática mediante el uso remedios neutrales con respecto al funcionamiento del mercado 40 explica, en primer lugar, porqué, desde sus orígenes 41 , la normativa de consumo ha consagrado el derecho a la información como un fundamento esencial de la protección contractual del consumidor tanto en su normativa general como sectorial 42 . Y, segundo, porqué las medidas encaminadas a proteger el consumidor vulnerable adoptan una estrategia basada en el recurso a los deberes de información 43 .…”
Section: Consumidores Y Usuarios Frente a Situaciones De Vulnerabilid...unclassified
“…Cude (2006) found most consumers had limited understanding of disclosures, and many participants said they were unlikely to read disclosures. Ben-Shahar and Schneider (2011) surveyed various studies of the effectiveness of consumer disclosures and found little impact. Isaccharoff (2011:59-60) noted that the "soft paternalism" of disclosure had little effect to improve poor decision-making, especially in light of behavioral insight in how consumers make decisions.…”
Section: Expected and Actual Benefits From Mandated Disclosures-a Lit...mentioning
confidence: 99%
“…Deze rationele consument leest algemene voorwaarden voordat hij of zij een overeenkomst sluit. Uit empirisch onderzoek blijkt dat dit in veel gevallen helemaal niet gebeurt (Ben-Shahar, 2009;Marotta-Wurgler & Taylor, 2013;Bakos, Marotta-Wurgler & Trossen, 2014;Ben-Shahar & Schneider, 2011;Schebesta & Purnhagen, 2020;Schmitz & Pavillon, 2020). Voor zover consumenten rationeel zijn in de zin van het Europese recht, zijn zij dat in begrensde mate (Van Witteloostuijn, 1988;Simon, 1990).…”
Section: Consumentenrechtunclassified